The hard, bloodless surface of a mirror: Patricia Highsmith’s Kierkegaardian anatomy of anxiety - Adams, Don (Literature and theology, 2024)
This essay considers Patricia Highsmith’s Ripley novels in relation to the philosophy of Søren Kierkegaard, which Highsmith knew and admired, and argues for the ethical earnestness of Highsmith’s fiction. The essay interprets Tom Ripley as an implicit allegorical expression of the Kierkegaardian demonic, which is the ultimate condition of the individual living in despair, without ethical purpose or existential possibility. When read from a Kierkegaardian existentialist perspective, the Ripley novel series is revealed as an extended ethical cautionary tale for the contemporary reader in a nihilistic age of anxiety.